The TanDEM-X Mission - Zink, Manfred; Krieger, Gerhard; Fiedler, Hauke; Moreira, Alberto (Committee on Earth Observation Satellites (CEOS), 2006)
TanDEM-X (TerraSAR-X add-on for Digital Elevation Measurement) is an innovative radar interferometry mission to generate a global, consistent and highly accurate Digital Elevation Model (DEM) and to provide a configurable SAR interferometry platform for demonstrating new SAR techniques and applications. This paper summarizes the mission concept starting from the mission objectives, the HELIX orbit and TanDEM-X operational modes to the expected height performance. Examples of new SAR techniques are presented. The TanDEM-X mission has been approved for full implementation by the German Space Agency. The launch is planned for spring 2009.
DLR Import::2019-04-03